The epilogue [compact disc] - Lewis, Dean, 1987- (Capitol, 2024)
Global superstar Dean Lewis releases his hotly anticipated third studio album via Capitol Records. Dean will head off on a global tour to support the album release. The Epilogue Tour will start in Australia in October 2024 and head to the US, UK, and EU in 2025. The 12-track album includes his previous singles, Trust Me Mate and Memories, as well as the recently released All I Ever Wanted.